Types and Eruption Patterns of the Carboniferous Volcanic Edifices in the Shixi Area, Junggar Basin - Yiming, Abulimiti; Bian, Baoli; Liu, Longsong; Chen, Hailong; Shan, Xuanlong; Li, Ang; Yi, Jian (Frontiers in Earth Science, 2022)
The types of volcanic edifices and volcanic eruption patterns control the accumulation and distribution of oil and gas. By means of drillings, seismic data, and geochemical analysis, the types and distribution of the Carboniferous volcanic edifices in the Shixi area of Junggar Basin were studied, the formation mechanism of magma was clarified, and the eruption patterns of volcanoes were investigated. The results show that the types of the Carboniferous volcanic edifices in the Shixi area mainly include stratovolcanic edifices, shield basic volcanic edifices, and mound superimposed volcanic edifices. Stratovolcanic edifices and mound superimposed volcanic edifices are developed around the Shixi fault, while single stratovolcanic edifices are developed around the Mobei fault. Shield basic volcanic edifices are only developed in the south of the Shixi area. Vertically, volcanic edifices are mainly developed on the hanging walls of the faults. When the faults develop, the volcanic vents are dendritic, forming mound superimposed volcanic edifices in space. On the plane, there are more volcanic edifices in the Shixi salient than in the Mobei salient. Intermediate-acid volcanic edifices are distributed in beaded shapes along one side of the Shixi fault and the Mobei fault, while basic volcanic edifices are distributed in sheet shapes on both sides of the Dinan fault. In the early Carboniferous, the Shixi area was in the island arc environment under the subduction of the oceanic crust. The basic magma came from the melting of the subduction plate, and the intermediate-acid magma came from the partial melting of the crust. In the late Carboniferous, the extensional environment formed by the retraction of the subduction plate led to the formation of large-scale volcanic eruptions. The extensional environment formed by the retreat of the subduction plate in the later stage resulted in large-scale volcanic eruptions.